A Never-Ending Presidential Election - LI, Daniel Ling (Journal of Research for Christianity in China (JRCC), 2025)
This article examines the impact of the 2020 U.S. election from three perspectives: globalization's disruption of traditional American society, the negative consequences of secularization for the United States, and the challenges facing Biden in the post-Trump era. It highlights how Trumpism will constrain the future trajectory of both the United States and U.S.-China relations, arguing that while the election has nominally concluded, it has in fact merely ushered in the opening act of profound transformation.